IMPLEMENTASI PASAL 9 PERATURAN DAERAH KOTA PONTIANAK NOMOR 10 TAHUN 2010 TENTANG KAWASAN TANPA ROKOK TERHADAP MAHASISWA DAN DOSEN YANG MEROKOK DI LINGKUNGAN KAMPUS (Studi Pada Universitas Tanjungpura Pontianak) - SISCA UTHARI NIM. A1011151186 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACT Smoking Free Areas are closed places or rooms that are declared prohibited for smoking, selling, advertising and/or promoting cigarettes. The scope of the Non-Smoking Area includes: public places, places of work, places of worship, children's playgrounds, public transportation, environments where teaching and learning processes take place, and health facilities. Therefore, the Pontianak City Government issued Pontianak City Regional Regulation Number 10 of 2010 concerning Smoke-Free Areas and prohibited everyone from smoking in Smoke-Free Areas as stipulated in Article 9, which stipulates that: